The Project Performance Evaluation of PLBN Project Using Earned Value Management Method - Malsya Debrina Nur Salsabila; Ika Arum Puspita; Sandhy Widyasthana (School of Industrial and System Engineering, Telkom University, 2022)
Process of monitoring and controlling projects requires data evaluation activities in the order to find out whether the project is in accordance with the plan to avoid an incompatibility between the planning and the actual time. The failure of construction project almost reached the figure of 20% - 40% which occurred in the project monitoring and controlling process. The purpose of this research is analysis project performance with earned value management method at PLBN Project. This research was carried out by several stages: data collection, data processing and analysis. From the results of the performance index analysis show that the project’s performance on the construction project is still not good. At week 16 the CPI and SPI values are 0.94 and 0.85. Both values can be interpreted that the costs incurred are greater than planning and the implementation time is longer than planning. The result of EAC is Rp. 2.423.695.294 with an estimated completion time is 21 weeks which indicates that there is an additional 3 weeks of completion.